2020
DOI: 10.4102/sajhrm.v18i0.1294
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological capital and self-leadership strategies on job embeddedness in the banking industry

Abstract: Orientation: The success of organisations depends on their ability to appoint, develop, sustain and retain skilled employees. Retaining a strongly committed workforce has become a top priority for most organisations in the financial service sector. Nurturing positive organisational behaviours and emotions helps retain employees, and this is key to lowering the risk of losing precious talent.Research purpose: The purpose of the study was to determine if self-leadership and psychological capital positively influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(102 reference statements)
0
4
0
1
Order By: Relevance
“…Prior research has considered PsyCap as a necessary antecedent of organizational embeddedness (e.g. Harunavamwe et al, 2020). According to MRTT, we suggest that the degree of leaderfollower PsyCap congruence may impact followers' organizational embeddedness.…”
Section: Psycap Congruence and Organizational Embeddednessmentioning
confidence: 80%
See 1 more Smart Citation
“…Prior research has considered PsyCap as a necessary antecedent of organizational embeddedness (e.g. Harunavamwe et al, 2020). According to MRTT, we suggest that the degree of leaderfollower PsyCap congruence may impact followers' organizational embeddedness.…”
Section: Psycap Congruence and Organizational Embeddednessmentioning
confidence: 80%
“…Prior research has considered PsyCap as a necessary antecedent of organizational embeddedness (e.g. Harunavamwe et al. , 2020).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Vai trò của OCB ngày càng trở nên quan trọng để giúp doanh nghiệp tồn tại và phát triển. Điều này được phản ánh qua thực tế, khi mà Tổng Liên đoàn Lao động Việt Nam luôn kêu gọi người lao động hãy đồng cam, cộng khổ, làm việc trách nhiệm, tận tâm hơn 8 thiện tình trạng nghỉ việc của nhân viên 9 . Kết quả từ các nghiên cứu cho thấy vấn đề nghỉ việc của nhân viên còn ảnh hưởng xấu lên văn hóa tổ chức và tinh thần của các nhân viên khác 10 .…”
Section: Tổng Quan Nghiên Cứuunclassified
“…Over the years, the high turnover rate of employees in the banking industry has been one of the major concerns in scientific studies because of the centrality of employees to the success, competitiveness and sustainability of their organisations (Harunavamwe et al 2020). Turnover intention [TI], defined as the probability that an employee will voluntarily leave his/her job within a specified time period, predicts actual turnover behaviour, a construct of great importance due to the impending shortage of competent employees needed to facilitate organisational work (Albalawi et al 2019;Martin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The growing competition has exacerbated the challenges to talent retention practices, especially in the banking sector, where skills shortages have become more prominent (Joāo and Coetzee 2011). Harunavamwe et al (2020) argue that the cost-cutting measures adopted by banks have made them an undesirable work environment for highly competent and talented employees. In fact, Cole (2017) observed that over 48 percent of employees in the banking industry are actively searching for external job opportunities, while approximately 30 percent of these employees have been employed for less than a year.…”
Section: Introductionmentioning
confidence: 99%